Discourse on the Characteristic of Tafsir Ruhu’l-Ma’ani - Suraju, Saheed Badmus (ADDIN, 2018)
A lot of works have been written on Tafsīr of the noble Qur’ān with their various characteristics that distinguish them from one another. Some focused on the use of traditions (Riwāyah) while some others focus on the use of acquired knowledge (Dirāyah) or opinion- based Tafsīr (Ra’y). This study focused on one of the most popular works on Tafsīr bir-Ra’y entitled Rūḥu’l-Ma’āni fi Tafsīri’l-Qur’āni’l-’Azīm was-Sab’i’l-Mathānī (The Insightful Meaning of the Exegesis of the glorious Qur’ān and the Seven Reoccurrence). The paper aimed at bringing out the hidden treasure of this encyclopedic work of Tafsīr to the English audience including its features and the sources of its information. The method adopted in this research is basically analytical and exegetical method. Findings revealed that Rūḥu’l-Ma’āni has some characteristics that stand it out among other works of Tafsīr such as logical connection between verses and chapters, grammatical analysis of verses and verification of hadīth among others. It was also revealed that the author relied on many books and scholars of different fields in his Tafsīr which makes the book a compendium of Tafsīr, and an inevitable reference material for contemporary Qur’ānic commentators. The paper concluded by recommending that the contemporary scholars and students of Tafsīr should create awareness on the significance of the tafsir book by using it in tafsir session and carrying out further research on it as well as making it an additional source of information while explaining the glorious Qur’ān.